Autism Spectrum Disorder Prediction - S, Shanthi; K, Nirmaladevi; M, Pyingkodi; S, Nithyaprakash (International Journal of Psychosocial Rehabilitation, 2020)
Autism Spectrum Disorder (ASD) is a syndrome that affects neurons and person’s interaction, communication and learning skills. Detecting autism behavior through screening tests is very expensive and time consuming. Mostly ASD were seen from the children in age group of 2-14. This ASD has more chances to get cured but it will take more than 5 years of required treatment. The ASD will predict only by the doctors and they only give the required treatment for patient’s earlier designation and correct medication at the first stage is extremely essential to manage ASD.ASD prediction framework is build to support interactive aspect based analysis model without any device. Machine learning techniques such as random forest, Artificial Neural Network have been utilized to improve the diagnosis accuracy. The ASD prediction process is focused on the childhood and adolescent’s analysis model is utilized in the system.